La experiencia de Perú con un programa nacional de bancos de sangre - José Fuentes Rivera Salcedo; Oscar Roca Valencia (Revista Panamericana de Salud Pública, 2003)
This paper describes Peru's experiences with its National Blood Banking Program. Until the mid-1990s, the country faced a host of problems, including the lack of a legal framework to regulate blood banks, a high maternal mortality rate due to a shortage of blood, virtually no voluntary donations, a high risk of infection from transfusions, the use of only whole blood for transfusion, serious disorganization in the blood banks, deficiencies in blood bank supervision and control, no training programs, indifference on the part of health officials, frequent selling of blood, and limited community awareness. Subsequently, a strategic plan was prepared that made it possible to solve many of those problems. Legal instruments were prepared; the rate of voluntary donations rose from 0% to 19.5%; the safety of the blood was improved through compulsory screening of all donated blood units for seven markers of infectious diseases, as well as by placing a national seal of quality on all screened units. The availability of blood doubled, thus meeting 70% of the need; sales of blood decreased; and the use of blood components was improved, with 80% of the blood being fractionated. In addition, supervisory control of 100% of the blood banks in the country was achieved, a national registry was established, the cost-benefit relationship for blood units was improved through centralized screening, internal and external quality control was made mandatory, and prodonation campaigns led to commitments from civil society. While important, all these achievements represent just a first step. This is especially true given that developing the National Blood Banking Program required the participation of outside organizations, such as the Pan American Health Organization, whose support, together with the experience provided by other countries, was key. The Program is facing a number of new challenges, and the progress that has been achieved could be threatened if current activities stagnate or if officials become complacent.